Meğazi'nin Kur'an tefsiri'ne kaynaklığı (Begavi'nin Mealimü't-Tenzili örneği) - Kaya, Aykut (My University, 2009)
Megazi, Beğavi, Meâlimü’t-Tenzîl ÖZET Meğazi’nin Kur’an Tefsiri'ne Kaynaklığı (Begavi’nin Mealimü’t-Tenzili Örneği) Begâvi’nin Mealimü’t-Tenzili tefsirinde Meğazi’nin Kur’an tefsirine nasıl kaynaklık ettiği konusunun ele alındığı bu çalışma, birinci bölümde Begâvi’nin hayatı, eserleri ve tefsiri hakkında bilgilere yer verdik. İkinci bölümde, Meğâzi ilmi hakkında genel bilgilerin yanında Megâzi’nin Kur’an tefsirine nasıl kaynaklık ettiğini metodolijik açıdan ele aldık. Üçüncü bölümde ise Begâvi’nin Meğâzi rivayetlerini hangi metot uyguladığını ve bunları hangi amaçlarla kullandığını tespit etmeye çalıştık. Sonuç itibariyle bu tez, tarih ilminin bir şubesi olan meğazinin klasik tefsir literatüründe Kur’an tefsirine kaynaklığını metodolojik açıdan incelenmesidir. Megazi, Begavi, Meâlimü’t-Tenzîl.

Source of Megazi to the Qur’an-commentary (In the Context of Beğavî’s Commentary Entitled Meâlimü’t-Tenzîl) The subject matter of thesis is about how source of Megazi is for the the Qur’an-commentary in the context of Beğavî’s commentary entitled Meâlimü’t-Tenzîl. The thesis consists of an introduction, three main parts, and a conclusion. The introduction gives brief information about the subject of the study, its purpose, importance, method, and resources which are used in the thesis. The first part analyzes Beğavî’s life, intellectual background, his works, and especially his commentary entitled Meâlimü’t-Tenzîl. The second part includes some about science of Megazi. In addition to this, the matter of how source of Megazi is for the the Qur’an-commentary is discussed methodologically. The third part of the thesis examines transmissions which exist in Beğavî’s commentary entitled Meâlimü’t-Tenzîl. Moreover, the chapter includes the analysis of the transmissions in Meâlimü’t-Tenzîl in point of their method and point. Opinions obtained during the study are mentioned in the conclusion. Consequently, this thesis is a research about source of Megazi which is a science of history to Qur’an commentary in the classical Qur’an-commentary literature .
Keywords: İslam Dini; Tefsir